Trophic Dynamics of Zooplankton Before and After Polar Night in the Kongsfjorden (Svalbard): Evidence of Trophic Position Estimated by δ15N Analysis of Amino Acids - Choi, Hyuntae; Ha, Sun-Yong; Lee, Seunghan; Kim, Jee-Hoon; Shin, Kyung-Hoon (Frontiers in Marine Science, 2020)
In polar ecology, zooplankton diets and survival rates vary according to the seasonality of solar radiation and oceanographic conditions. Each zooplankton species has evolved feeding strategies to survive in the diet-limited conditions of the “polar night”. Many zooplankton studies have reported seasonal adaptations in feeding activity during polar night based on their trophic niches. Nitrogen isotope analysis of amino acids has provided improved accuracy in estimates of trophic position (TP) in various marine species. In this study, field work was conducted in Kongsfjorden before (October 2017) and after polar night (April 2018). As representative zooplankton, an amphipod (Themisto abyssorum), euphausids (Meganycitiphanes norvegica and Thysanoessa sp.), a chaetognath (Parasagitta elegans), and copepods (Calanus spp. and Oithona similis) were collected. TP values of each taxon were estimated using the nitrogen isotope ratio of glutamic acid (δ15NGlu) and phenylalanine (δ15NPhe). Results showed that TP values of P. elegans were relatively constant, averaging 3.2 in both seasons, likely due to continuous feeding activity during polar night. TP values were also constant for Calanus spp., ranging 2.5 to 3.0 in both seasons due to the ability to utilize stored high-energy wax. In contrast, average TP values for O. similis, an omnivorous zooplankton, were 2.9 in October and 2.3 the following April. TP values for O. similis before polar night can be attributed to the relatively high availability of algae during longer periods of daylight. We found that TP variation in zooplankton before and after polar night differed according to feeding activities in diet-restricted circumstances.